Rev binds specifically to a purine loop in the SL1 region of the HIV-1 leader RNA. - Gallego, J; Greatorex, J; Zhang, H; Yang, B; Arunachalam, S; Fang, J; Seamons, J; Lea, S; Pomerantz, R; Lever, A (2003)
The leader RNA sequence of human immunodeficiency virus type 1 (HIV-1) consists of a complex series of stem loop structures that are critical for viral replication. Three-dimensional structural analysis by NMR of one of these structures, the SL1 stem loop of the packaging signal region, revealed a highly conserved purine rich loop with a structure nearly identical to the Rev-binding loop of the Rev response element. Using band-shift assays, surface plasmon resonance, and further NMR analysis, we demonstrate that this loop binds Rev. HIV-1 appears to have a second Rev-binding site close to the major splice donor site that may have an additional role in the viral life cycle.